Wpływ przepisów unijnych na przemysł drobiarski w Polsce - Sikorska, Daria (Influence of EU Regulations on Polish Poultry Section, 2005)
Sanitary standards in the EU poultry market are one of the highest. Healthy and sanitary standards concern: production of hens, chickens and eggs; buildings and equipment and people working on poultry farms.Polish poultry section has to conform itself to the EU market regulations. For poultry companies and farms this means changes in veterinary, sanitary and environmental regulations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 270-274